(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: OSA is a sleep related breathing disorder that characterized by a decrease or complete absent in airflow despite an ongoing effort to breathe. It occurs through relaxation and collapse of the muscles of upper air way during sleep, this leads to partial reductions (hypopneas) and complete absent (apneas) in breathing that last at least 10 seconds during sleep. Most pauses last between 10 and 30 seconds, but some may persist for one minute or longer. This leads to critical reductions in blood oxygen saturation, with oxygen levels falling as much as 40 percent or more in severe cases. OSA is caused by repetitive bouts of upper airway obstruction during sleep as a result of the narrowing of respiratory passages. The most common site of obstruction is the nasopharynx. The diagnosis of obstructive sleep apnea syndrome (OSAS) requires both assessment of clinical features and objective demonstration of sleep disordered breathing. Patients usually present with loud habitual snoring, witnessed apnea, and excessive daytime sleepiness. Inspite of the high prevalence of OSAS in the general population (at least 4% of males and 2% of females), the condition is usually unrecognized as patients often regard their symptoms as normal variants or a manifestation of poor lifestyle